Eduphobia – an emerging business? - Abdul Razak, Dzulkifli (Sun Media Corporation Sdn Bhd, 2019)
I READ a book recently that alleges Islamophobia is now a new “business”. There is money to be made by “selling” Islamophobia through literature, talk shows, conferences and the like. There are markets for people who will never get tired speaking about it and hearing of the same. And then get worked up depending on how paranoid they are. This, however, is good for the organisers bent on feeding the frenzy and exploiting such emotions and situations while they laugh all the way to the bank.